Engaging Men to Transform Inequitable Gender Attitudes and Prevent Intimate Partner Violence : A Cluster Randomised Controlled Trial in North and South Kivu, Democratic Republic of Congo - Vaillant, Julia; Koussoubé, Estelle; Roth, Danielle; Pierotti, Rachael Susan; Hossain, Mazeda; Falb, Kathryn L (BMJ Global Health, 2022)
Globally, one in three women worldwide report experiencing intimate partner violence (IPV) in their lifetime. The study objective was to understand the effectiveness of Engaging Men through Accountable Practice (EMAP), a group-based discussion series which sought to transform gender relations in communities, on intimate partner violence (IPV), gender inequitable attitudes and related outcomes. Interventions engaging men have the potential to change gender attitudes and behaviours in conflict-affected areas. However, while EMAP led to changes in gender attitudes and behaviours related to perpetration of IPV, the study showed no overall reduction of women’s experience of IPV. Further research is needed to understand how working with men may lead to long-term and meaningful changes in IPV and related gender equitable attitudes and behaviours in conflict areas.